Development of Biomimetic Hydroxyapatite Containing Dental Restorative Composites - Aydinoglu, Aysu; Turkcan, Julide Hazal; Kelesoglu, Ergun; Yoruc, Afife Binnaz Hazar (SPRINGER HEIDELBERG, 2022)
The aim of the study was to evaluate the incorporation effect of biomimetic hydroxyapatite (BHA) particles on the mechanical properties of experimental dental composites. Two experimental composites were produced from the same organic matrix, Si/Zr nanocluster, and SiO2/silane as main inorganic reinforcing fillers. 7wt% BHA was added to one of the groups to evaluate its effect on mechanical properties. The BHA was also modified with 3-MPTMS to improve chemical bonding. Chemical structures and physical properties of the fillers were identified by XRD, FTIR, XPS, TGA, SEM, BET, and Zeta-Sizer. According to ISO 4049 and DIN 50,133 the mechanical properties, and to ISO 10993-5:2009 the biocompatibility was investigated. Analysis of variance (ANOVA) was used for the statistical analysis of acquired data. The BHA was synthesized by the biomimetic method in simulated body media (SBF). The SEM images of BHA/Silane particles demonstrated rod-like shapes and similar dimensions with natural hydroxyapatite present in tooth enamel. The modification by using 3-MPTMS was decreased the mean particle size of the fillers due to a lower agglomeration tendency. Moreover, the addition of small mass fractions of the BHA into the dental resins can substantially meet the ISO 4049 requirements. Consequently, the BHA was not adversely decreasing the mechanical properties of the dental composites. Also, the biocompatibility of the BHA-containing composites was found better than the samples without BHA-containing composites. The incorporation of the BHA can meet the mechanical requirements of dental resins and composites. Additionally, it may show regenerative properties against small lesions.
Keywords: Biomimetic hydroxyapatite; Silanization; Dental composite; Mechanical properties; In vitro cytotoxicity; MECHANICAL-PROPERTIES; PRECIPITATION; REINFORCEMENT; NANOPARTICLES; ADHESIVE; STRENGTH; POWDERS; FILLERS; AGENTS; RESINS; Science & Technology - Other Topics